Actividad de dos triazoles diferentes en un modelo murino de paracoccidioidomicosis - Restrepo, Susana (1992)
A new orally absorbable triazole (Schering 39304) with a long serum half-life in man (60 hours), was tried in a murine model of progressive paracoccidioidomycosis and compared with itraconazole, another triazole which has proven effective in this mycosis. Only 15% of the infected, untreated mice survived while 53 to 75% of the animals receiving itraconazole survived. Mice treated with Schering 39304 exhibited higher (86 - 100%) survival rates. Statistically, the 5 mg/kg Sch 39304 was superior to the 50 mg/kg itraconazole dose. Lung cultures showed that 20 mg/kg/day of Sch achieved sterilization of the infectious foci. These results indicate that the new triazole will have a place in the treatment of paracoccidioidomycosis